The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3389/fnagi.2017.00075
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Selectively Regulated Prioritization Shift Depending on Walking Situations in Older Adults

Abstract: Background: Older adults have increased risks of balance issues and falls when walking and performing turns in daily situations. Changes of prioritization during different walking situations associated with dual tasking may contribute to these deficits. The objective of this study was therefore to investigate whether older adults demonstrate changes of prioritization during different walking paths.Methods: In total, 1,054 subjects with an age range from 50 to 83 years were selected from the first follow-up vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 56 publications
2
13
0
Order By: Relevance
“…Higher cognitive-related motor DTEs were found for the task with higher cognitive load (the greater the cognitive load, the higher the motor interferences). The magnitude of the motor interference is comparable to the results of Salkovic et al ( 2017 ), where subjects had to walk around a circle on the floor. The cognitive interferences, however, are many times higher in our dual task paradigm.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Higher cognitive-related motor DTEs were found for the task with higher cognitive load (the greater the cognitive load, the higher the motor interferences). The magnitude of the motor interference is comparable to the results of Salkovic et al ( 2017 ), where subjects had to walk around a circle on the floor. The cognitive interferences, however, are many times higher in our dual task paradigm.…”
Section: Discussionsupporting
confidence: 86%
“…Hence, the measure of change of direction walking provides different and meaningful information about daily life walking ability than walking on straight pathways alone (Lowry et al, 2012 ). Salkovic et al ( 2017 ) were able to demonstrate that a priorization of resource allocation is influenced by the walking situation. According to their results older adults with poor cognitive flexibility exhibit a tendency to riskier walking behavior during more complex walking situations, compared to older adults with good cognitive flexibility.…”
Section: Introductionmentioning
confidence: 99%
“…According to a previous study [39], these findings demonstrated that even in healthy older people additional attention resources are required for obstacle crossing and recovering from an obstacle crossing step. Whereas walking on curved paths is considered more difficult than that on straight paths, older adults with poor cognitive flexibility tend to exhibit risky walking behavior during more complex walking situations compared to older adults with good cognitive flexibility [40]. In this sense, deficits in higher-order cognitive processing may limit obstacle negotiation abilities in people with MCI, being a potential falls risk [41].…”
Section: Discussionmentioning
confidence: 99%
“…The second dataset (HE dataset) consisted of 172 healthy elderly individuals (78 females, average age 70.1 years ± 6.2) assessed during the third visit (2013/14) of the TREND study (Salkovic et al, 2017). Only subjects without functionally relevant disturbance of balance or locomotor function were included.…”
Section: Methods Subjects and Clinical Assessmentsmentioning
confidence: 99%